ANALYSIS OF THE EFFECT OF DISTANCE BETWEEN TRANSMITTER AND RECEIVER COILS IN WIRELESS PHOTOVOLTAIC POWER TRANSFER SYSTEMS - Balatif, Muhammad Iqbal; Irwanto, Muhammad; Gultom, Togar Timoteus; Nainggolan, Winner Parluhutan; angin, Despaleri Perangin-; karo, Muhammad Azlin Karo-; Zebua, Tenuman (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2024)
Wireless power transmission technology can eliminate the use of cables, thereby increasing the mobility, convenience and security of electronic devices for all users. The wireless photovoltaic power transfer system will be modeled using Mathlab Simulink software built by a PV module, half-bridge inverter, transmitter and receiver coils. The distance between the transmitter and receiver coils is changed from 1 m to 10 m. PVWPT (Photovoltaic Wireless Power Transfer) is a system that combines photovoltaic (PV) technology and wireless power transfer to transfer electrical energy from a PV module to a receiving device or system without using physical cables. By using PVWPT, electrical energy can be generated from sunlight by PV modules and wirelessly transferred to receiving devices that require power. The farther the distance, the less voltage will be sent. And the error percentage is 5%.